Choriocapillaris Changes Are Correlated With Disease Duration and MoCA Score in Early-Onset Dementia - Zhang, Shuting; Kwapong, William Robert; Yang, Tang; Liu, Peng; Tuo, Qingzhang; Cheng, Yajun; Li, Xue; Liu, Ming; Lei, Peng; Wu, Bo (Frontiers in Aging Neuroscience, 2021)
Purpose: Imaging of the choroid may detect the microvascular changes associated with early-onset dementia (EOD) and may represent an indicator for detection of the disease. We aimed to analyze the in vivo choriocapillaris flow density and sub-macula thicknesses in EOD patients using optical coherence tomography angiography (OCTA) and evaluate the association with its clinical measures. Methods: This cross-sectional study used the OCTA to image and analyze the choriocapillaris (CC) of 25 EOD patients and 20 healthy controls. Choriocapillaris flow density in the 3mm area and 6mm area was measured by an inbuilt algorithm in the OCT tool. Brain volume using magnetic resonance imaging and cognitive assessment was done and recorded. RESULTS: Significantly reduced capillary flow density of the choriocapillaris was seen in EOD patients when compared to healthy controls in the 3.0 mm (P = 0.001) and 6.0 mm (P < 0.001) area respectively. MoCA scores in EOD patients positively correlated with choriocapillaris flow density in the 3mm area (Rho = 0.466, P = 0.021). Disease duration of EOD patients also negatively correlated with choriocapillaris density in the 3mm area (Rho = -0.497, P = 0.008). DISCUSSION: Our report suggests that choriocapillaris damage may be a potential indicator of early-onset dementia. Microvascular impairment may be involved in the early phase of dementia without aging playing a role in its impairment.